Around the independence´s meaning abstract - Fontana Lázaro, Josep (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This relective article does an analysis about the historic-graphics discourses which have been built on the independence process. These explain the participation of the social actors and the popular masses. The question is: How does the independence process generated, and what way the social actors are related?.